Analisis Pengaruh Indikator Keuangan dan Makroekonomi Terhadap Profitabilitas Bank Pekreditan Rakyat di Masa Sebelum dan Selama Pandemi Covid-19 - Doni Rahmad; Fajri Adrianto; Masyhuri Hamidi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the influence of CAR, LDR, CASA, PDRB, and Inflation on the profitability of 82 (eighty-two) Rural Credit Banks (BPR) in the West Sumatra Province presented in the form of ROA ratios during the period before the Covid pandemic from 2017 to 2019 and during the Covid pandemic period from 2020 to 2022. The research method employed is descriptive research with a quantitative approach, utilizing panel data regression analysis. The data used are secondary data sourced from the financial reports of BPR publications in the West Sumatra Province, the Central Bureau of Statistics, and Bank Indonesia. Partial results of the research during the pre-Covid pandemic period indicate that (1) CAR significantly influences ROA positively; (2) LDR significantly influences ROA negatively; (3) CASA significantly influences ROA negatively; (4) PDRB significantly influences ROA negatively; (5) Inflation does not significantly influence ROA. Simultaneously, CAR, LDR, CASA, PDRB, and Inflation collectively significantly affect ROA of BPR in the West Sumatra Province during the pre-Covid pandemic period. Partial results during the Covid pandemic period indicate that (1) CAR significantly influences ROA positively; (2) LDR does not significantly influence ROA; (3) CASA does not significantly influence ROA; (4) PDRB significantly influences ROA negatively; (5) Inflation does not significantly influence ROA. Simultaneously, CAR, LDR, CASA, PDRB, and Inflation collectively significantly affect ROA of BPR in the West Sumatra Province during the Covid pandemic period.